Pengaruh Pembinaan Toleransi Antar Umat Beragama Pada Mahasiswa di Kota Gorontalo - Ibnu Rawandhy N. Hula; Fatimah Djafar; Mujahid Damopolii; Ana Mariana; Abdul Rohman (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This study describes tolerance among religious communities and intolerant behavior in students. It also tests the hypothesis of whether there is a significant influence between fostering tolerance among religious communities and heterogeneous student behavior in the formal educational institutions in Gorontalo City. The study used quantitative research with a correlation method through a simple regression. Data were collected using a closed questionnaire, which involved 67 students. This study showed that there is a significant influence between fostering religious tolerance and intolerant behavior of students. This influence is shown by the regression coefficient number of F-count 115.577 with a significance level of 5% (F-table = 3.99). Besides, the value of determination (R Square) = 0,640 illustrates that tolerance among religious communities has a high effect on the tolerance behavior of students. Thus, it can be stated that 64% of the students’ tolerance behavior is affected by the religious communities’ tolerance, and the rest (36%) is influenced by other factors.